Pengaruh Strategi Predict, Organize, Rehearse, Practice and Evaluate (PORPE) terhadap Keterampilan Membaca Pemahaman Siswa di Kelas V SDN 10 Sungai Sapih - Sintia Ulandari; Annisa Kharisma; Riri Marfilinda (ARZUSIN, 2025)
The low level of reading comprehension skills among fifth-grade students at SDN 10 Sungai Sapih forms the background of this study, primarily due to reading instruction that minimally engages prediction processes, resulting in students struggling to answer questions and draw conclusions from texts. This research aims to analyze the effect of the Predict, Organize, Rehearse, Practice, and Evaluate (PORPE) strategy on students’ reading comprehension skills. A quasi-experimental method with a posttest-only control group design and a quantitative approach was employed. Data were analyzed using a t-test, which revealed that the t-value exceeded the critical value (4.272 > 1.676), indicating the rejection of H₀ and acceptance of H₁. The main findings demonstrate that the PORPE strategy has a significant effect on improving students' reading comprehension skills. The study concludes that the PORPE strategy is effective in reading comprehension instruction. Theoretically, this research contributes to the body of knowledge on cognitively based reading strategies, while practically, it serves as a reference for teachers and schools in implementing more structured and strategic literacy approaches. Additionally, this study opens avenues for further exploration of PORPE strategy implementation across different educational levels and learning contexts.